Continuous thermosalinograph oceanography along RV SONNE cruise track SO289 - Eric Pieter Achterberg; Michael Schlundt (PANGAEA, 2023)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after 24 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. Salinity was calibrated for each box independently against discrete water samples (see additional attachment). No temperature calibration was performed. For details to all processing steps see Data Processing Report.